Failure analysis of Monastery of Jerónimos, Lisbon: how to learn from sophisticated numerical models - Lourenço, Paulo B. (2007)
Conservation and restoration of historical structures are still a challenge to modem practitioners even if significant research advances have occurred in the last decades. Significant advances have been made in non-destructive testing, mechanical characterization, tools for advanced numerical analysis, knowledge on traditional materials and techniques, and innovative materials and techniques. In the paper, Monastery of Jero´nimos in Lisbon, Portugal is adopted as a case study for structural safety assessment. A first discussion is held on the difficulties related to the need of adopting simplified geometries of the model. After a set of sophisticated non-linear failure analyses, a second discussion is held with respect to the consequences associated with the results obtained. Finally, additional in situ testing and monitoring are carried out in a truly iterative process of knowledge accumulation before defining any remedial measures.